Effects of GI Meals on Intermittent Exercise - Hulton, A. T.; Gregson, W.; Maclaren, D.; Doran, D. A. (International Journal of Sports Medicine, 2012)
Pre-exercise meals or single foods containing low glycaemic index (LGI) carbohydrates (CHO) have been shown to enhance performance prior to prolonged steady state exercise compared to high glycaemic index (HGI) CHO. This study investigated the impact of HGI and LGI pre-exercise meals on intermittent high intensity exercise. Nine male recreational football players performed a football specific protocol followed by a 1 km time trial 3.5 h after ingesting 1 of 2 isoenergetic test meals (HGI: 870.3 kcal, LGI: 889.5 kcal), which were either HGI (GI: 80) or LGI (GI: 44). Blood glucose, fatty acids (FA), glycerol, β-hydroxybutyrate, lactate and insulin were assessed before, during, and after the exercise bout, whilst rates of CHO and fat oxidation were determined at 4 time points during the protocol. No significant differences were found for the 1 km time trial (LGI: 210.2±19.1 s: HGI: 215.8±22.6 s) (mean±SD), nor for any of the other variables measured (P>0.05) apart from a significant condition effect with FA and significant interaction effects observed for glucose, β-hydroxybutyrate and lactate (P<0.05). These findings suggest that the type of CHO ingested in a pre-match meal has no significant impact on performance or metabolic responses during 90 min of intermittent high intensity exercise.
Keywords: pre-exercise nutrition; carbohydrates; glycaemic index; football-simulated exercise